Modeling of Free-Space Optical Communications in Aviation - Durali, Ataberk; Unverdi, N. Ozlem (IEEE, 2023)
Free-space optical (FSO) communication systems, whose applications in early aviation are in the form of experimental studies, have gained importance with the increasing influence of unmanned aerial vehicles in the field today. In this study, a four-channel FSO communication mechanism between the ground station and aircraft is modeled with the OptiSystem 7.0 simulation program. The effects of multiplexing structures, amplifiers, filters, time delay and phase shift on the quality factor of the setup were investigated.
Keywords: Communication technologies; free-space optical communications; laser; multiplexing; amplifier; Computer Science; Communication; Engineering; Telecommunications